Prioritising determinants of organizational performance in hotel industry: an empirical investigation for Bangladesh - Islam, Rafikul; Rahman, Mahbubar (2018)
The study develops a hierarchical model which prioritizes the quality determinants to enhance organizational performance in the hotel industry of Bangladesh. The study followed a mixed method approach. The study utilised the qualitative approach through semi structured interviews with 16 top and middle level hotel executives to identify the required quality determinants which contributes on hotel’s organisational performance. Afterwards, prioritisation of the identified determinants and their corresponding sub-determinants were done by applying the Analytic Hierarchy Process (AHP) in quantitative stage. A total of 26 hotel executives were considered here as respondents. The qualitative stage surfaced eight determinants namely: top management commitment and leadership, strategic planning, service process management, employee focus, customer/guest focus, quality management, communication and business results as well as their corresponding sub-determinants. The results of AHP indicate that quality management is ranked most important followed by communication and customer/guest focus as second and third ranked in importance to enhance the organizational performance. With regard to sub-criteria, it is found that to resolve the most important criteria, i.e., quality management, hoteliers should consider the health and safety-security measures as most important issues followed by environment management. In the case of the criterion communication, management should give more emphasis on internet/digital service. For the criterion customer/guest focus, hotels should more concern about customer/guest satisfaction as well as customer/guest relationship management. The findings can be used by practitioners to measure performance of hotels. Though the study was conducted in the context of Bangladesh, however, it can be applied to measure performance of hotels in other countries as well with minor modifications. Moreover, Human Resource Development (HRD) professionals and scholars can use these findings for designing and implementing appropriate HRD policies to enhance organizational performance.